Data-driven Development of ROTEM and TEG Algorithms for the Management of Trauma Hemorrhage: A Prospective Observational Multicenter Study - Baksaas-Aasen, Kjersti; Van Dieren, Susan; Balvers, Kirsten; Juffermans, Nicole P; Næss, Pål A; Rourke, Claire; Eaglestone, Simon; Ostrowski, Sisse R; Stensballe, Jakob; Stanworth, Simon; Maegele, Marc; Goslings, J C; et al. (Annals of surgery, 2019)
Developing pragmatic data-driven algorithms for management of trauma induced coagulopathy (TIC) during trauma hemorrhage for viscoelastic hemostatic assays (VHAs). Admission data from conventional coagulation tests (CCT), rotational thrombelastometry (ROTEM) and thrombelastography (TEG) were collected prospectively at 6 European trauma centers during 2008 to 2013. To identify significant VHA parameters capable of detecting TIC (defined as INR > 1.2), hypofibrinogenemia (< 2.0 g/L), and thrombocytopenia (< 100 x10/L), univariate regression models were constructed. Area under the curve (AUC) was calculated, and threshold values for TEG and ROTEM parameters with 70% sensitivity were included in the algorithms. A total of, 2287 adult trauma patients (ROTEM: 2019 and TEG: 968) were enrolled. FIBTEM clot amplitude at 5 minutes (CA5) had the largest AUC and 10 mm detected hypofibrinogenemia with 70% sensitivity. The corresponding value for functional fibrinogen (FF) TEG maximum amplitude (MA) was 19 mm. Thrombocytopenia was similarly detected using the calculated threshold EXTEM-FIBTEM CA5 30 mm. The corresponding rTEG-FF TEG MA was 46 mm. TIC was identified by EXTEM CA5 41 mm, rTEG MA 64 mm (80% sensitivity). For hyperfibrinolysis, we examined the relationship between viscoelastic lysis parameters and clinical outcomes, with resulting threshold values of 85% for EXTEM Li30 and 10% for rTEG Ly30.Based on these analyses, we constructed algorithms for ROTEM, TEG, and CCTs to be used in addition to ratio driven transfusion and tranexamic acid. We describe a systematic approach to define threshold parameters for ROTEM and TEG. These parameters were incorporated into algorithms to support data-driven adjustments of resuscitation with therapeutics, to optimize damage control resuscitation practice in trauma.